2018
DOI: 10.1016/j.appet.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

The family child care home environment and children's diet quality

Abstract: Foods and beverages served, in addition to nutrition education and nutrition policies in family child care homes, may be promising intervention targets for improving child diet quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 46 publications
6
41
0
1
Order By: Relevance
“…The finding that total HEI scores (overall diet quality) did not improve is not expected. Overall HEI scores in children in both states were relatively low (about 60 out of 100 possible points) but consistent with prior observations of children's dietary intake in ECE centers [21,[52][53][54] and family child care homes [55,56]. In these studies, consistent with our findings, children scored highest in whole fruit, total fruit, and dairy components.…”
Section: Discussionsupporting
confidence: 91%
“…The finding that total HEI scores (overall diet quality) did not improve is not expected. Overall HEI scores in children in both states were relatively low (about 60 out of 100 possible points) but consistent with prior observations of children's dietary intake in ECE centers [21,[52][53][54] and family child care homes [55,56]. In these studies, consistent with our findings, children scored highest in whole fruit, total fruit, and dairy components.…”
Section: Discussionsupporting
confidence: 91%
“…Secondary outcomes include changes in FCCH practices from the pre-post surveys and the EPAO and changes in FCCH nutrition and activity environments from the EPAO. This analysis will assess the overall EPAO nutrition score and subscales created by the UNC originators of the tool [102].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, nearly 50% of vegetables consumed in ECE were fried potatoes, and only 8% were the more nutrient-dense dark green or brightly colored vegetables [15]. Other studies of young children in the US and the Netherlands have found similar results [14,[16][17][18]. In the UK, limited data suggest that children are also served insufficient quantities of fruits and vegetables.…”
Section: Introductionmentioning
confidence: 85%